Most Effective Management Style for Modern Workplace - Adil Namiq, Frya (International Journal of Engineering and Management Sciences, 2018)
There are managers who are coaches, who are democratic, who are dictatorial and those who are consensus builders. All styles come with positives and negatives, many managers employ a combination of all to make progress. Ultimately, the managers that have the most successful teams are the ones who help each individual member of the team to grow. To manage the best way possible, you need to be strict but gentle and, employees will probably feel good and happy in a medium where inclusivity is a need. Balance in the work environment is imperative for empowering employees from all background to feel certain about their potential and accomplish their best. The higher the self-esteem, the more beneficial the employees are. People from different background can offer variety of abilities and experiences, aptitudes and encounters that might be of advantage to the organization and their work execution. Although some hybrid of aptitudes can be gainful with regards to helping each other, a mixture of skills and abilities among the group likewise implies that workers can gain from each other. By working nearby individuals of various backgrounds, experiences and working styles, creative ideas can be conceived then discussed among each other and offering feedback and proposals. Though one individual might be extraordinary at out of the box thoughts, another individual may have the important experience to execute it; so it is fundamental to play on every individual's skills, abilities and work together within the group.